Práticas epistêmicas em atividades investigativas de Ciências - Nascimento, Elton Daniel Oliveira do (2015)
This study joins the prospect that students acquire an adequate conception of the nature of science, and for this, it is considered that the argument in science classrooms is essential to spread this knowledge. This research aims to analyze the development of epistemic practices over investigative activities in Physics in high school classrooms, explaining its relationship with the actions of the teacher to conduct such activities. Among the existing analytical tools in the literature, it highlights the epistemic practices defined in Duschl and Kelly (2002), based on studies of Philosophy, Sociology and Anthropology of Science, the authors define the epistemic practices as specific ways in which members of a scientific community , understand, justify, evaluate and validate the developed knowledge. Jimenez-Aleixandre and Bustamante (2007) consider the notion of epistemic practice presented in Kelly and Duschl (2002) and Sandoval (2001) to say that the epistemic practices relate to social practices in intrinsic relationship to knowledge, and prepare a set of epistemic practices associated with social activities of production, communication and evaluation of the knowledge presented in Kelly (2005). This concept is already being worked on other research, and in them we find categories that characterize the speech of scientific content of the students, but this work seeks to contemplate a larger number of categories in order to contribute to advancing this discussion and for a better view epistemic practices and investigative activities become a segment that helps in the analysis. An investigative activity, with a well-crafted script and with the collaboration of the teacher in his driving, facilitates the development of epistemic practices by students. In this sense, the data analyzes were collected in a workshop of Physics entitled "Investigating the thermal expansion of solids," developed into a science popularization event, this investigative sequence occurred in the Application School of the Federal University of Sergipe, which seeks to analyze driving teacher in developing these research activities, using the categories: communication approaches, teacher's intentions and epistemic movements. For the analysis of epistemic practices of students, we rely on the categories proposed by Jiménez-Aleixandre and Bustamante (2007) and works that dialogue with this. Thus, it is a relationship of these actions with the epistemic practices developed by students and, considering the results, it was apparent that the teacher's actions, combined with the activity of the structure, favored the emergence of some epistemic practices by students, primarily in production instance of knowledge. Moreover, it is noted that the structure of investigative activity is important for the conceptual evolution of the students and the subsequent absorption of the scientific knowledge.